Penggunaan Media Gambar Untuk meningkatkan Hasil Belajar IPA Siswa Kelas V SD Islam Unggulan Hidayatul Mubtadiin Daya Murni - Hayati; Yuda Seta Mahendra (Indonesian Journal of Integrated Science and Learning, 2024)
The problems of this research are low student involvement in learning, lack of media use in learning and low student learning outcomes. This study aims to determine the improvement of science learning outcomes of fifth grade students of SD Islam Unggulan Hidayatul Mubtadiin Daya Murni using picture media. The research includes classroom action research (PTK) with 3 cycles. The subjects of this study were 28 fifth grade students of SD Islam Unggulan Hidayatul Mubtadiin Daya Murni. Data collection was carried out through tests and descriptive data analysis. The results showed that the use of picture media can improve students' science learning outcomes, namely in the pre-cycle 10.71%, cycle I 53.57%, and cycle II 85.71%. The results of the study above can be concluded that the use of picture media is effective in improving science learning outcomes of fifth grade students of SD Islam Unggulan Hidayatul Mubtadiin Daya Murni.